The emerging role of microRNAs in bone diseases and their therapeutic potential - Bravo Vázquez, Luis Alberto; Moreno Becerril, Mariana Yunuen; Mora Hernández, Erick Octavio; León Carmona, Gabriela García de; Aguirre Padilla, María Emilia; Chakraborty, Samik; Bandyopadhyay, Anindya; Paul, Sujay (MDPI, 2021)
MicroRNAs (miRNAs) are a class of small (20–24 nucleotides), highly conserved, non-coding RNA molecules whose main function is the post-transcriptional regulation of gene expression through sequence-specific manners, such as mRNA degradation or translational repression. Since these key regulatory molecules are implicated in several biological processes, their altered expression affects the preservation of cellular homeostasis and leads to the development of a wide range of pathologies. Over the last few years, relevant investigations have elucidated that miRNAs participate in different stages of bone growth and development. Moreover, the abnormal expression of these RNA molecules in bone cells and tissues has been significantly associated with the progression of numerous bone diseases, including osteoporosis, osteosarcoma, osteonecrosis and bone metastasis, among others. In fact, miRNAs regulate multiple pathological mechanisms, including altering either osteogenic or osteoblast differentiation, metastasis, osteosarcoma cell proliferation, and bone loss. Therefore, in this present review, aiming to impulse the research arena of the biological implications of miRNA transcriptome in bone diseases and to explore their potentiality as a theragnostic target, we summarize the recent findings associated with the clinical significance of miRNAs in these ailments.